BEYOND THE ORGANIZED CRIME: THE REFORMULATION OF THE INSURGENCY CONCEPT AND ITS IMPACT ON THE SOUTH AMERICA’S STRATEGIC SURROUNDINGS - Bartolomé, Mariano (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The Latin America’s geographic space is prodigal with non-conventional threats to the security of the states, the societies and the individuals which integrate it. These threats are characterized by their transnational dynamics, the non-state character of their protagonists and the asymmetrical use of violence. Inside this outlook we can highlight the organized criminality, which is present in every region of the hemisphere, showing different features in each case. The case of Mexico can be emphasized because of its gravity, typified by research centers and experts as an example of a new form of insurgency. This readings force us to reformulate the concept of insurgency, defining it with more attention to the question of territorial control than the political motivation of its acts. Based on the outlook described, the objective of this paper is to apply the reformulation of the concept of insurgency to the South America’s scenario. In order to do this, the scope of this concept will be established, concrete cases of application will be identified, as well as their impacts on the regional strategic surroundings and the multilateral cooperation about security.